Aeromonas salmonicida induced immune gene expression in Aloe vera fed steelhead trout, Oncorhynchus mykiss (Walbaum) - Zanuzzo, F. S. [UNESP]; Urbinati, E. C. [UNESP]; Rise, M. L.; Hall, J. R.; Nash, G. W.; Gamperl, A. K. (Elsevier B.V., 2015)
Products derived from Aloe vera are popular around the world because of their cosmetic and medicinal properties, including immunostimulatory effects, and may have beneficial uses in aquaculture. Thus, we evaluated how feeding steelhead trout (Oncorhynchus mykiss, Walbaum) A. vera powder affected their basal immune function and immune response to formalin-killed atypical Aeromonas salmonicida (ASAL). Fish were sampled (n = 12) after being fed for 6 weeks with two diets [control and the same diet with 5 g kg(-1) A. vera (0.5%) added], and 3 (n = 12) and 24 (n = 12) hours after both groups received an intraperitoneal injection of ASAL or saline (PBS). Parameters measured included growth, spleen-somatic index, respiratory burst of circulating leukocytes, serum lysozyme concentration, complement system activity (alternative pathway), and the transcript expression of several important immune-related genes (interleukin-1 beta, interleukin-8, tumor necrosis factor-alpha 1, tumor necrosis factor-alpha 2, cathelicidin-1, cathelicidin-2, ferritin heavy chain and interferon regulatory factor 1) in the spleen. Neither growth (mass gain) nor spleen-somatic index were affected by six weeks of feeding with A. vera. Similarly, dietary A. vera inclusion had no effect on: 1) the respiratory activity of blood leukocytes, serum lysozyme concentration, or complement systemactivity; 2) the constitutive expression of the assayed immune-related genes; or 3) ASAL-induced mRNA expression of any of the selected genes. This latter finding was despite the fact that injection of ASAL resulted in a very robust immune response; similar to 3 to 1500 fold increases in the expression of all 8 immune-related genes. These data suggest that the prolonged feeding of salmonids with A. vera in an aquaculture setting will not enhance their ability to resist bacterial infection, or diminish the impact of bacterial diseases once infected. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aloe vera; Steelhead trout; Immune response; Innate immunity; Immunostimulant; Gene expression